Cross-Activity Analysis of CRISPR/Cas9 Editing in Gene Families of Solanum lycopersicum Detected by Long-Read Sequencing - Ofri Kutchinsky; Dongqi Li; Guy Assa; Asaph Aharoni; Zohar Yakhini (Current Issues in Molecular Biology)
CRISPR/Cas9 genome editing holds promise for precise genetic modifications, yet off-target effects remain a concern—particularly in gene families with high sequence similarity. In this study, we present a computational framework for analyzing editing specificity and cross-reactivity in gene families using long-read sequencing data. The pipeline integrates multiplex PCR, NGS, and CRISPECTOR-based analysis to detect and quantify on- and off-target events with high sensitivity. As a use case, we applied this framework to Solanum lycopersicum, evaluating on-target editing in thirteen gene families and analyzing off-target cross-reactivity in five representative families. While the biological results are illustrative, the primary contribution lies in the generalizable analysis approach, which can support genome editing studies in complex plant genomes and beyond.